2024
DOI: 10.5194/egusphere-2024-115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vegetation Response to Climatic Variability: Implications for Root Zone Storage and Streamflow Predictions

Nienke Tessa Tempel,
Laurene Bouaziz,
Riccardo Taormina
et al.

Abstract: Abstract. This paper investigates the influence of multi-decadal climatic variability on the temporal evolution of root zone storage capacities (Sr,max) and its implications for streamflow predictions at the catchment scale. Through a comprehensive analysis of 286 catchments across Europe and the US, we analyse the deviations in evaporative ratios (IE) from expected values based on catchment aridity (IA) and their subsequent impact on Sr,max predictions. Our findings reveal that while catchments do not strictl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The overall estimated magnitudes fall with S umax ~ 95 -115 mm well within the range of long-term average values reported previously for the greater region (e.g. Bouaziz et al, 2021;Hrachowitz et al, 2021;Tempel et al, 2024) and other temperate, humid environments (e.g. Kleidon, 2004;Gao et al, 2014b;de Boer et al, 2016;Wang-Erlandsson et al, 2016;Stocker et al, 2023;van Oorschot et al, 2023).…”
Section: Multi-decadal Changes In Root Zone Storage Capacity Sumaxsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall estimated magnitudes fall with S umax ~ 95 -115 mm well within the range of long-term average values reported previously for the greater region (e.g. Bouaziz et al, 2021;Hrachowitz et al, 2021;Tempel et al, 2024) and other temperate, humid environments (e.g. Kleidon, 2004;Gao et al, 2014b;de Boer et al, 2016;Wang-Erlandsson et al, 2016;Stocker et al, 2023;van Oorschot et al, 2023).…”
Section: Multi-decadal Changes In Root Zone Storage Capacity Sumaxsupporting
confidence: 88%
“…precipitation and transpiration (e.g., Donohue et al, 2012;Gentine et al, 2012;Gao et al, 2014b;De Boer-Euser et al, 2016;Nijzink et al, 2016a;Dralle et al, 2021;McCormick et al, 2021;Hrachowitz et al, 2021;Stocker et al, 2023;van Oorschot et al, 2021van Oorschot et al, , 2023. For applications of hydrological and land-surface models S umax (or equivalent parameters) has, except for very few exceptions (Wagener et al, 2003;Merz et al, 2011;Bouaziz et al 2022;Tempel et al, 2024) been assumed constant over time. As a major knowledge gap, it remains so far unknown if S umax follows climatic variability and evolves over time, thereby reflecting vegetation adaptation to changing conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…precipitation and transpiration (e.g., Donohue et al, 2012;Gentine et al, 2012;Gao et al, 2014b;De Boer-Euser et al, 2016;Nijzink et al, 2016a;Dralle et al, 2021;McCormick et al, 2021;Hrachowitz et al, 2021;Stocker et al, 2023;van Oorschot et al, 2021van Oorschot et al, , 2023. For applications of hydrological and land-surface models S umax (or equivalent parameters) has, except for very few exceptions (Wagener et al, 2003;Merz et al, 2011;Bouaziz et al 2022;Tempel et al, 2024) been assumed constant over time. As a major knowledge gap, it remains so far unknown if S umax follows climatic variability and evolves over time, thereby reflecting vegetation adaptation to changing conditions.…”
mentioning
confidence: 99%
“…However, several studies have demonstrated that catchments in many regions world-wide experience deviations ΔI E from their expected new I E following a change in I A (e.g. Jaramillo and Destouni 2014;van der Velde et al, 2014;Jaramillo et al, 2018a;Reaver et al, 2022;Tempel et al, 2024).…”
mentioning
confidence: 99%